KESESUAIAN INSTRUMEN EVALUASI DENGAN MATERI PLANTAE YANG DIAJARKAN GURU DI SMA BANDUNG - Sepita Ferazona; Adi Rahmat; Siti Sriyati (Universitas Lampung, 2015)
Evaluation instrument for measuring the ability of the students must be in accordance with the basic competencies, so that the competencies expected to be achieved. This study from the aspect of material suitability evaluation instruments with the material submitted by teachers during the learning process in the classroom. The method used in this research was descriptive method. Subjects were six biology teachers of the seven high schools in Bandung as samples, each school representing the three clusters. Selection of the samples was conducted using stratified sampling technique, by selecting the category of schools with high, medium and low. Basic competencies were analyzed Plantae material of X grade. The data obtained by observation, documentation and questionnaire study. The suitability of material evaluation instruments with the material submitted by teachers during the learning process in the classroom at Plantae material that is equal to 83.88%.Keywords: basic competencies, evaluation instrument, learning outcomesInstrumen evaluasi dalam mengukur kemampuan siswa harus sesuai dengan kompetensi dasar, agar kompetensi yang diharapkan bisa tercapai. Penelitian ini dilihat dari aspek kesesuaian materi instrumen evaluasi dengan materi yang disampaikan guru selama proses pembelajaran di kelas. Metode yang digunakan dalam penelitian ini adalah metode deskriptif. Subjek penelitian adalah enam orang guru biologi dari tujuh SMAN di kota Bandung sebagai sampel, setiap sekolah mewakili tiga cluster. Pemilihan sampel penelitian ini dilakukan dengan menggunakan teknik stratified sampling, yaitu dengan memilih sekolah dengan katagori tinggi, sedang dan rendah. KD yang dianalisis materi Plantae kelas X. Data diperoleh dengan cara observasi, studi dokumentasi dan angket. Kesesuaian materi instrumen evaluasi dengan materi yang disampaikan guru selama proses pembelajaran di kelas pada materi Plantae yaitu sebesar 83,88%.Kata kunci: hasil belajar, instrumen evaluasi, kompetensi dasar